Improving mathematic communication ability through islamic math e-comic media: A study on building flat sides - Suri, Fraulein Intan; Anggoro, Bambang Sri; Komarudin, Komarudin; Fahmi, Rohmah Romadhona (Universitas Islam Negeri Raden Intan Lampung, 2022)
Media Islamic Math e-Comic is a mathematical comic with Islamic nuances that has mathematical problem solving with clear illustrations and problem-solving methods according to indicators that can improve students' mathematical communication skills. This study aims to determine how much the increase in mathematical communication skills in the use of Islamic Math e-Comic media on the subject of flat side space for class VIII. The media is developed through stages in the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This type of research is Quasy Experiment by giving pretest and posttest questions on small-scale tests and large-scale tests. Then, the effectiveness test of the use of Islamic Math e-Comic media was carried out using the Effect Size test, obtaining results of 0.53 with the